Angiofibroma Beyond the Nasopharynx: Diagnostic Challenges and Endoscopic Management of Two Atypical Cases Arising from the Ethmoid and Sphenoid Sinuses - Dolly Irfandy; Bestari Jaka Budiman; Jihan Mudrika Rahmi; Auzy Yoana Khalisha; Hippocrates Kam (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Angiofibroma is a histologically benign but locally aggressive vascular neoplasm almost exclusively associated with the nasopharynx of adolescent males (Juvenile Nasopharyngeal Angiofibroma, JNA). Extranasopharyngeal angiofibroma (ENA) is an exceptionally rare variant that originates outside the sphenopalatine foramen, posing significant diagnostic and management challenges due to its atypical locations, age of presentation, and clinical mimicry of other sinonasal pathologies. Case presentation: We present two sophisticated cases of ENA managed at our tertiary center. Case 1: A 35-year-old male presented with unilateral nasal obstruction. Endoscopy and imaging revealed a hypervascular mass centered in the posterior ethmoid sinus, destroying the basal lamella and abutting the skull base. Histopathological analysis was initially confounded by features resembling a solitary fibrous tumor (SFT), requiring a comprehensive immunohistochemical panel (IHC) including STAT6 and nuclear beta-catenin to confirm the diagnosis of angiofibroma. Case 2: A 17-year-old male presented with symptoms and imaging (non-contrast CT) highly suggestive of a benign sphenochoanal polyp. An initial attempt at routine endoscopic removal was aborted due to unexpected, profuse hemorrhage. Subsequent advanced imaging (CTA/MRI) revealed a hypervascular sphenoid-based angiofibroma. Both patients underwent preoperative superselective embolization followed by successful, purely endoscopic tumor resection with no recurrence at 12 and 18-month follow-up, respectively. Conclusion: ENA is a critical, albeit rare, diagnostic consideration for any vascular sinonasal mass, regardless of patient age or tumor location. These cases underscore the unreliability of "classic" clinical and radiological signs, the diagnostic pitfalls of histopathological mimics like SFT and polyps, and the critical role of advanced IHC (nuclear beta-catenin) for definitive diagnosis. A modern, multidisciplinary approach combining preoperative embolization with endoscopic resection offers a safe and effective pathway to cure.